2014
DOI: 10.1007/s40097-014-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked poly(vinyl alcohol)/sulfonated nanoporous silica hybrid membranes for proton exchange membrane fuel cell

Abstract: Organic-inorganic nanocomposite membranes of poly(vinyl alcohol) (PVA) and nanoporous silica containing sulfonic acid groups are synthesized in order to increase the proton conductivity, water retention and thermal stability of membrane. The cross-linked PVA/ SBA-15-propyl-SO 3 H nanocomposite membrane was prepared by solution casting method. Infrared spectroscopy and scanning electron microscopy are used to characterize and confirm the structure of PVA and the cross-linked membranes. The impedance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
1
29
1
Order By: Relevance
“…1 confirm these results. Similar results for water uptake have been observed in previous work [12,13,32]. The results obtained from water uptake measurements of BaZrO 3 nanoparticles demonstrated that those BaZrO3 nanoparticles displayed a 9% water uptake in 25°C.…”
Section: Water Uptake and Proton Conductivity Measurementssupporting
confidence: 90%
See 1 more Smart Citation
“…1 confirm these results. Similar results for water uptake have been observed in previous work [12,13,32]. The results obtained from water uptake measurements of BaZrO 3 nanoparticles demonstrated that those BaZrO3 nanoparticles displayed a 9% water uptake in 25°C.…”
Section: Water Uptake and Proton Conductivity Measurementssupporting
confidence: 90%
“…In previous studies, we introduced new proton conducting hybrid membranes for PEM fuel cells based on poly(vinyl alcohol) and nanoporous silica containing phenyl or propyl sulfonic acid [12,13] and poly(vinyl alcohol) and poly(sulfonic acid)-grafted silica nanoparticles [14,15]. Recently, the preparation and characterization of Nafion/ Fe 2 TiO 5 nanocomposite membranes for proton exchange membrane fuel cells (PEMFCs) were investigated [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to prevent drying of the membrane and keep the membrane at most conductive state, without external humidification, many composite membranes with self-humidifying ability have been developed. For example, incorporating hygroscopic metal oxides, such as silica [17][18][19][20][21], titania [13,[22][23][24], zeolites [25,26] montmorilonite [27], iron titanate [28], zirconia [29], strontium cerate [30] and barium zirconate [31,32] were developed to absorb water and accordingly improve the proton conductivity. These prepared nanocomposite membranes have presented good interfacial compatibility, enhanced water retention property and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike a few other biopolymers, PVA neither causes deforestation nor affects food supply . It is also used as a material for proton exchange membranes and pervaporation systems, in biomedical and drug delivery applications and in composites …”
Section: Introductionmentioning
confidence: 99%